Emotion regulation and positive affect in the context of salivary alpha‐amylase response to pain in children with cancer. Issue 6 (19th January 2018) - Jenkins, Brooke N.; Granger, Douglas A.; Roemer, Ryan J.; Martinez, Ariana; Torres, Tara K.; Fortier, Michelle A.
Abstract: Background: Children with cancer routinely undergo painful medical procedures invoking strong physiological stress responses. Resilience to this pain may be conferred through resources such as emotion regulation strategies and positive affect. Procedure: This study measured dispositional positive affect in children with cancer (N = 73) and randomly assigned participants to one of three emotion regulation strategy conditions (distraction, reappraisal, or reassurance). Children applied their assigned strategy during an experimental pain procedure (the cold pressor task [CPT]) and provided saliva samples before, immediately after, and 15 min after the CPT. Saliva samples were later assayed for salivary alpha amylase (sAA)—a surrogate marker for autonomic/sympathetic nervous system activity and regulation. Results: Children in the reassurance group had sAA levels that continued to rise after completion of the CPT compared to children in the distraction ( b = –1.68, P = 0.021) and reappraisal conditions ( b = –1.24, P = 0.084). Furthermore, dispositional positive affect moderated the effect of condition such that children in the reassurance group with lower levels of positive affect had sAA levels that continued to rise after completion of the CPT (dy/dx = 1.56, P = 0.027), whereas children in the reassurance condition with higher levels of positive affect did not exhibit this rise ( P > 0.05). Conclusions: Specific emotion regulation strategies, such as distraction and reappraisal, may attenuate the stress response to pain in pediatric patients with cancer, and positive affect may confer resilience in response to pain even with use of less effective coping strategies such as reassurance.